Antimicrobial resistance in humans and livestock population in India - SEN, ARNAB; BANDOPADHYAY, SAMIRAN; MISRI, JYOTI; CHAUHAN, H C; KUMAR, P ANAND; VAID, R K; DUTTA, T K; DUBAL, Z B; SHOME, B R; K SINGH, R; BHATIA, RAJESH; KUMAR, ASHOK; et al. (The Indian Journal of Animal Sciences, 2022)
Antimicrobial resistance (AMR) is considered as one of the biggest threats to modern civilization. The reviewis published with a view to provide awareness about this growing menace, which if not monitored and controlledcould lead to major public health consequences with greater economic impact. Very little data and information isavailable regarding AMR in livestock and aquaculture. An attempt was made to collate the available information onAMR subsequent to constitution of INFAAR (Indian Network on Fishery and Animals Antimicrobial Resistance) byICAR and FAO, in reference to National Action Plan on AMR by GoI in April, 2017.